1980
DOI: 10.1007/bf00025127
|View full text |Cite
|
Sign up to set email alerts
|

Correlated resistance of cassava to mosaic and bacterial blight diseases

Abstract: INDEXWORDSManihot esculenta, cassava, Manihot glaziovii, ceara rubber, Xanthomonas manihotis, cassava bacterial blight, cassava mosaic disease, heritability, genotypic correlation, correlated response to selection. SUMMARYThe two most serious diseases ofcassava (Manihot esculenta CRANTZ) are cassava mosaic disease (CMD) and cassava bacterial blight (CBB) (Xanthomonas manihotis STARR). Clone 58308, derived from the third backcross of the interspecific cross of cassava (M. esculenta) x ceara rubber (M. glaziovii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…The detection of markers SSRY44 and NS136 having association with CMD resistance is a new report indicating the possibility of having another genetic loci for CMD resistance in cassava in addition to the already established on linkage group G (Fregene et al, 1997). This finding supports the polygenic control of resistance to CMD as established by Hahn et al (1980aHahn et al ( , 1980b.…”
Section: Simple Sequence Repeat (Ssr) Analysissupporting
confidence: 66%
See 1 more Smart Citation
“…The detection of markers SSRY44 and NS136 having association with CMD resistance is a new report indicating the possibility of having another genetic loci for CMD resistance in cassava in addition to the already established on linkage group G (Fregene et al, 1997). This finding supports the polygenic control of resistance to CMD as established by Hahn et al (1980aHahn et al ( , 1980b.…”
Section: Simple Sequence Repeat (Ssr) Analysissupporting
confidence: 66%
“…The studies conducted by Hahn, Howland, and Terry (1980a) ;Hahn, Terry, and Leuschner (1980b) to establish the genetics of resistance to CMD indicated the possibility of several genes responsible for resistance. Akano, Dixon, Mba, Barrera, and Fregene (2002) reported that the resistance could be due to a major dominant gene (CMD2).…”
Section: Introductionmentioning
confidence: 99%
“…The clone 58308-with low cyanide potential and resistance to ACMV-was used as a source of resistance to CBB. An important research finding was that CBB resistance derived from M. glaziovii was associated with CMD resistance (Hahn et al 1980b). Furthermore, this IITA breeding endeavor led to new hybrid clones with resistance to CBB and ACMV, plus high yield and acceptable tuberous root quality traits (Hahn et al 1989).…”
Section: Cassavamentioning
confidence: 99%
“…Because of the low correlations between the performance at this early stage of selection and when the genotypes reach replicated trials, the early selections are based on high-heritability traits such as plant type, branching habits and, particularly, reaction to diseases (Hahn et al, 1980a(Hahn et al, , 1980bHershey, 1984;Iglesias and Hershey, 1994;Morante et al, 2005). The second stage of selection is called Clonal Evaluation Trial (CET).…”
Section: Breeding Schemementioning
confidence: 99%
“…Many examples of sources of resistance to diseases (Hahn et al, 1980a;1980b) and pests (Bellotti et al, 2002), or desirable root quality traits (Ceballos et al, 2007b; have been identified. However, the impact of these high-value characteristics is limited because their introgression requires breeding a new variety de novo.…”
Section: Possibility Of Implementing the Back-cross Schemementioning
confidence: 99%